STUDENTS’ ANALYSIS ON PUNCTUATION AND CAPITALIZATION IN ARGUMENTATIVE TEXT - Kartika, Ayumi; Syaprizal, Syaprizal; Ramasari, Maria (Universitas Negeri Surabaya, 2024)
This research aims to determine how many errors are made by second-semester students in the English study program at PGRI Silampari University. This research design is qualitative with descriptive method. Data collection techniques used test, especially test in punctuation and capitalization. The technique of analyzing data with steps: 1. Identifying errors, 2. Classifying errors, 3. Describing errors, and Making Conclusion of errors. The results of this research showed that 91.30% of students who made error in punctuation: comma; 82.60% of students who made errors in punctuation: period; 65.22% of students who made errors in punctuation: apostrophe; 86.96% of students who made errors in punctuation: question marks; and 95.65% of students who made errors in punctuation: colon. Furthermore, the data showed that 78.26% and 82.60% of students who made errors in capitalization: all proper nouns or adjectives and title, heading, and sub heading; and only 34.78% of students who made errors in capitalize the first letter of the beginning word of sentence. From the data, it can be concluded that, there were many students who still did not know or master the use of punctuation and capitalization.